1995
DOI: 10.1128/mcb.15.12.6513
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylase- and ras-Induced Cell Transformations: Reversal by Protein Tyrosine Kinase Inhibitors and Role of pp130CAS

Abstract: We have found that overexpression of human ornithine decarboxylase (ODC) induces cell transformation in NIH 3T3 and Rat-1 cells (M. Auvinen, A. Paasinen, L. C. Andersson, and E. Hölttä, Nature (London) 360:355-358, 1992). The ODC-transformed cells display increased levels of tyrosine phosphorylation, in particular of a cluster of 130-kDa proteins. Here we show that one of the proteins with enhanced levels of tyrosine phosphorylation in ODC-overexpressing cells is the previously described p130 substrate of pp60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 53 publications
(71 reference statements)
3
53
0
1
Order By: Relevance
“…4). Pretreatment with 0.5 µg/mL of herbimycin A, a potent inhibitor of protein tyrosine kinases, particularly of the Src family, [32][33][34] decreased Src kinase activity below detectable levels and inhibited tyrosine phosphorylation of these 120-to 130-kd proteins in TGF-␤ 1 -treated Mahlavu cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…4). Pretreatment with 0.5 µg/mL of herbimycin A, a potent inhibitor of protein tyrosine kinases, particularly of the Src family, [32][33][34] decreased Src kinase activity below detectable levels and inhibited tyrosine phosphorylation of these 120-to 130-kd proteins in TGF-␤ 1 -treated Mahlavu cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…ODC also has been shown to be a critical component in cell transformation (Auvinen et al, 1992;Moshier et al, 1993). More recent work has shown that ODC expression induces enhanced level of tyrosine phosphorylation, in particular of p130 cas (Auvinen et al, 1995), suggesting that there is a protein tyrosine kinase(s) acting downstream of ODC either dependent or independent of its catalytic activity. The elevation of cellular polyamine levels induces antizyme production by a unique translational frameshifting mechanism (Rom and Matsufuji et al, 1995.…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable that c-myc and c-fos proto-oncogenes have been found to be transcriptional activators of ODC (Bello et al, 1993;Wrighton et al, 1993). More recently, it was reported that ODC expression induces an enhanced level of tyrosine phosphorylation, in particular of p130 cas (Auvinen et al, 1995), suggesting that there is a protein tyrosine kinase(s) acting downstream of ODC either dependent or independent of its catalytic activity. Thus, ODC and polyamines appear to play pivotal functions in the cellular signaling pathway for cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of activated Src to induce morphological transformation and anchorage-independent growth was restored when wild type Cas was ectopically expressed in the Cas-null cells. Furthermore, Auvinen et al (1995) demonstrated that expression of antisense Cas constructs could partially reverse cellular transformation induced by ornithine decarboxylase, Ha-Ras and v-Src, indicating that Cas plays a direct role in cellular transformation.…”
Section: Cancermentioning
confidence: 99%
“…Multiple proapoptotic stimuli have been shown to induce Cas cleavage, including Eschericia coli lipopolysaccharide (LPS), nocodazole, etoposide, adenosine and UV irradiation (Bannerman et al, 1998;Chan et al, 1999;Harrington et al, 2001;Kook et al, 2000a,b). Cas dephosphorylation, Cas cleavage and apoptosis are also induced by overexpression of the receptor-like PTPase LAR (Weng et al, 1999).…”
Section: Apoptosismentioning
confidence: 99%